1997
DOI: 10.3727/036012997816356725
|View full text |Cite
|
Sign up to set email alerts
|

Increased pain threshold following electroacupuncture: analgesia is induced mainly in meridian acupuncture points

Abstract: The pain threshold increased significantly in all tested sites after electroacupuncture but the analgesic effect was predominant in those points lying along the acupuncture meridians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 1 publication
2
14
0
1
Order By: Relevance
“…Interestingly, the rise in pain threshold appeared to be more prominent in acupuncture points tested along the acupuncture meridian than in non-acupuncture points further away from the meridian (Farber, Tachibana, & Campiglia, 1997).…”
Section: Acupuncture and Pain Reliefmentioning
confidence: 93%
“…Interestingly, the rise in pain threshold appeared to be more prominent in acupuncture points tested along the acupuncture meridian than in non-acupuncture points further away from the meridian (Farber, Tachibana, & Campiglia, 1997).…”
Section: Acupuncture and Pain Reliefmentioning
confidence: 93%
“…In six out of eleven studies (54.5%), threshold changes were more pronounced after ipsi-than after contralateral needling [25,34,67,[100][101][102]. In one high quality study bilateral needle placement was superior to unilateral needling [65], and results of three studies suggest that needle stimulation at LI 4 is more effective in changing pain thresholds than needling at other acupuncture points [39,53,65]. Four studies (20%) found significant effects of acupuncture on sensory perception independent of the needle location [28,60,66,75,95], and in two studies no change of any sensory threshold was observed [103,104].…”
Section: Effect Of Needle Location Relative To the Sites Of Measurementsmentioning
confidence: 96%
“…All showed a statistically significant elevation of the PPT through acupuncture. Two studies assessed the effect of EA only [28,39], three studies solely the effect of MA [65,95,98], and two the effect of both, MA and EA . Either a manual algometer [39,65,95,100] according to Fischer et al [107] or an electronic algometer [28,76,98] was used as measuring tool (tip size 1 cm 2 ).…”
Section: Ppt Assessed In Healthy Subjectsmentioning
confidence: 99%
See 2 more Smart Citations